Applicability of the German Food Based Dietary Guidelines for Infancy to Estimate Exposure to Substances in Food – The Example of Erucic Acid. (7th June 2021) - Kalhoff, Hermann; Kersting, Mathilde; Honermeier, Bernd; Jansen, Kathrin; Lücke, Thomas
Abstract: Objectives: The objective of this study was to use the recommended total daily food amounts of the German 'Dietary Scheme for the first year of life' (for the first time) to calculate the potential exposure of substances in the infant diet from a public health perspective. Erucic acid was taken as a concrete example, because the European Food Safety Agency (EFSA) recently issued a Tolerable Daily Intake (TDI) for erucic acid with a special note that vulnerable groups, especially young children, may be particularly at risk of exceeding the TDI. Methods: The age of about 1 month with the highest consumption per kg body weight was chosen for scenarios for the phase of exclusive milk feeding, the age of about 8 months for the CF phase. Principle of calculation was: erucic acid exposure = food consumption volume per kg bodyweight per day x erucic acid concentration in food (from European studies for breastmilk, EFSA food samples for formula, current German market analysis for rapeseed oil, EU food law). We calculated 6 scenarios for the milk phase (4 formula-feeding, 2 breastfeeding) and 8 scenarios for the CF phase (5 CF + formula-feeding, 3 CF + breastfeeding). Results: Out of the 14 scenarios, only 3 resulted in exposures in the safe range below the TDI (range 4.4.– 6.0 mg/kg BW). All scenarios assuming either high consumption (p95) or high concentration led to high exceedances of the TDI (range 7.5–26.2 mg/kg BW), especially when using maximum values of EU law for formula or vegetable oils (33.6 and 43.2 mg/kg BW respectively). Conclusions: The Dietary Scheme proved to be a suitable frame to calculate the potential exposure of substances in foods forming the daily infant diet. The results give cause for concern, as the calculated high exposure to erucic acid in the scenarios occurs during infancy as a particularly sensitive developmental period and results from the food-based recommendations as public health guidelines. Considering the scarcity of data, in addition to the proven low erucic acid concentrations in rapeseed oil in Germany, it is imperative to analyze the erucic acid content of mature breast milk and formula as well. Funding Sources: Union for the Promotion of Oil and Protein Plants (UFOP, Berlin, Germany).